Suggestion et réserve mentale - Aurélia Peyrical (Recherches Germaniques)
The aim of this paper is to shed light on two lesser-known aspects of Adorno’s work on philosophy: “mental reservations”, and the ability to “resist suggestion”. Both largely contribute to the Adornoian definition of philosophy as emancipatory practice. Philosophy therefore enables people to think for themselves and resist a strong suggestive social and political environment. They become more receptive to whatever situation they encounter. At the same time condition and result, “mental reservations”, and the ability to “resist suggestion” appear as key-features of the Adornoian plaidoyer for a philosophical thinking. They are also complementary, though not reducible, to other concepts in his work: for example, his concept of “primacy of the object” or his “immanent critique” methodology.